Hydrophobic Chitosan Derivatives for Gene and Drug Delivery in Cancer Therapies - Daria N. Poshina; Anna D. Rakshina; Yury A. Skorik (Polysaccharides)
Chitosan remains one of the most widely used biopolymers in biomedicine due to its non-toxicity and biodegradability. It is easily chemically modified, allowing its properties to be effectively altered to improve its performance as a gene and drug carrier. The introduction of hydrophobic moieties into chitosan can significantly enhance its interaction with cancer cells, improving its potential for targeted delivery. The hydrophobic moiety plays a crucial role in the interaction of the particle with the cell membrane during internalization by endocytosis. The type of hydrophobic moiety, its degree of substitution, and its placement along the chitosan backbone all influence the physicochemical properties and biological performance of the resulting polymer. Hydrophobic modification can also affect the self-assembly behavior of chitosan, influencing the size, shape, and stability of the resulting particles. These factors impact the loading efficiency of therapeutic agents and the release kinetics of the encapsulated cargo. While hydrophobic modification can enhance the therapeutic efficacy of chitosan, it is important to consider potential toxic effects. In summary, the hydrophobic modification of chitosan is a powerful strategy to improve its efficiency as a gene and drug carrier. By understanding the role of the hydrophobic moiety in cellular uptake, endosomal escape, self-assembly, and toxicity, researchers can design and develop optimized chitosan-based delivery systems for targeted cancer therapy.